Using information technology : a practical introduction to computers and communications - Williams, Brian K.; Sawyer, Stacey C. ;Hutchinson, Sarah E. (Chicago : Irwin Inc., 1995)
USING INFORMATION TECHNOLOGY: A Practical Introduction to Computers & Communications is designed for use as a college textbook to accompany a one-semester or one-quarter introductory course in computers or microcomputers. It is we hope, a book that will make a difference in the lives of our readers.
The digital age: the revolution in computers & communication -- Overview: getting a working knowledge of a computer & communications system -- Applications software: tools for thinking & working -- System software: the power behind the power -- Processors: hardware for power & portability -- Input & output: the human uses of computing & communications -- Storage & databases: foundations for interactivity, multimedia, & knowledge -- Communications: starting along the information highway -- Information systems: management & development -- Software development: programming & languages -- The promises of the digital age: agents, AI, & the I-Way -- The challenges of the digital age: civility, safety & security.
Includes bibliographical references (pages 595-601) and index.
Keywords: COMPUTERS